2002
DOI: 10.1159/000046989
|View full text |Cite
|
Sign up to set email alerts
|

The Next Step from High-Flux Dialysis: Application of Sorbent Technology

Abstract: The current foci of renal replacement therapy with dialysis are middle molecular weight toxins, consisting of small proteins, polypeptides and products of glycosylation and lipoxygenation. Conventional high-flux dialysis is not efficient at removing these molecules, explaining the increased interest in using sorbents to supplement dialysis techniques. Prototype biocompatible sorbents have been developed and investigated for middle molecule removal; these have been shown, in man, to remove β2-microgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…This is impractical, even at risk for hemodynamically unstable patients, such as septic shock. Meanwhile, it has been reported that the adsorptive resin was capable of signifi cantly removing middle molecular weight substances including various cytokines [22] . Ronco et al [23] developed and reported the continuous plasma fi ltration adsorption, a combination of plasma fi ltration and adsorption by resin.…”
Section: Discussionmentioning
confidence: 99%
“…This is impractical, even at risk for hemodynamically unstable patients, such as septic shock. Meanwhile, it has been reported that the adsorptive resin was capable of signifi cantly removing middle molecular weight substances including various cytokines [22] . Ronco et al [23] developed and reported the continuous plasma fi ltration adsorption, a combination of plasma fi ltration and adsorption by resin.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous venovenous hemofiltration (CVVH) with dialysis or continuous hemodiafiltration (CHDF) was first used for the treatment of hyper-cytokinemia in 1993 [46], and many of the subsequent efforts focused on this approach to improve outcomes in sepsis [46][47][48][49][50][51]. However, randomized controlled trials (RCTs) were unable to demonstrate clear outcome benefits with dialysis in patients with sepsis [52,53], and the inability to remove middle molecular weight toxins led to the need for supplementary hemoadsorption therapy [50,54,55].…”
Section: History Of Cytokine Adsorption Therapymentioning
confidence: 99%
“…The adsorptive resins used in the studies [36] described here (BetaSorb™ and CytoSorb™, RenalTech, New York, N.Y., USA), are capable of removing lowmolecular-weight protein toxins from blood, such as ß 2 -microglobulin, leptin, retinol-binding protein, complement factor D, IL-18 and angiogenin [37], as well as the proinflammatory cytokines TNF-·, IL-1ß, IL-6, IL-10 and TNF-· [38][39][40].…”
Section: Rationale For Sorbents In Arf and Esrdmentioning
confidence: 99%